2012
DOI: 10.1002/jbm.a.34318
|View full text |Cite
|
Sign up to set email alerts
|

Microgrooved patterns enhanced PC12 cell growth, orientation, neurite elongation, and neuritogenesis

Abstract: Understanding neurite outgrowth, orientation, and migration is important for the design of biomaterials that interface with the neuronal tissue. Micropatterns can significantly influence neurite outgrowth, neurite length, orientation, extracellular matrix expression, neuron differentiation, and migrating velocity. We analyzed the neuritogenesis and neurite outgrowth of PC12 cells in three-dimensional Si wafer with various micropatterns fabricated using photolithography and etching techniques. When nerve growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 31 publications
(32 reference statements)
3
36
2
Order By: Relevance
“…An ideal synthetic bone scaffold should support osteoblastic phenotype behavior, particularly, bone matrix deposition. Tissue scaffolds with microscale to nanoscale features support greater cellular adhesion and phenotypic activity than planar scaffolds [22][23][24]. Textured scaffolds mimic the highly featured native-tissue architecture exhibited in numerous natural tissues.…”
Section: Discussionmentioning
confidence: 97%
“…An ideal synthetic bone scaffold should support osteoblastic phenotype behavior, particularly, bone matrix deposition. Tissue scaffolds with microscale to nanoscale features support greater cellular adhesion and phenotypic activity than planar scaffolds [22][23][24]. Textured scaffolds mimic the highly featured native-tissue architecture exhibited in numerous natural tissues.…”
Section: Discussionmentioning
confidence: 97%
“…57 Su et al studied the effects of micropatterns on PC12 cell behaviors and found that the cells cultured on Si microgrooved patterns extended 2 to 3 times longer neurites on the micropatterns. 58 prefer differentiation (i.e., neurite formation) to proliferation, whereas the cells on the smooth substrate tend to induce proliferation rather than neurite formation. Regarding neurite elongation, in our study, no significant differences in neurite length were found between the wPPy and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 19 smooth PPy substrates during the early days of culture.…”
Section: Fabrication Of Wppy/pdmsmentioning
confidence: 97%
“…Extensive research to date has been performed on topographies in the micrometre range. Such studies reported neuronal alignment and axonal outgrowth, although the microgrooves reached supra-cellular dimensions (Tuft and et al, 2013;Clark and et al, 1990;Beduer and et al, 2012;Su and et al, 2013;Morelli and et al, 2010;Miller et al, 2002;Hirono and et al, 1988;Walsh et al, 2005). Several groups demonstrated a maximum pitch threshold for alignment and a negative correlation between alignment and increasing pitch size (Tuft and et al, 2013;Beduer and et al, 2012;Yao and et al, 2009).…”
Section: Discussionmentioning
confidence: 90%